Developing a model of working with worry in emotion‐focused therapy: A discovery‐phase task analytic study. Issue 1 (22nd October 2016) - Murphy, Jennifer; Rowell, Lucy; McQuaid, Anne; Timulak, Ladislav; O'Flynn, Rosie; McElvaney, James
Abstract: Background: Generalised anxiety disorder (GAD) is an anxiety disorder characterised by excessive anxiety and worry. Worry is seen as a key‐defining feature of GAD. Several cognitive‐behavioural models of working with worry in GAD exist. More recently, there have been efforts to adapt emotion‐focused therapy (EFT) for GAD. This study focused on task analysis, observing therapist and client processes (using qualitative observations as well as observer‐used measures) in the clinically developed, two‐chair dialogue for worry (an intervention inspired by a similar EFT task of working with self‐criticism in depression). Method: A task analysis methodological approach was applied to 34 worry dialogues from eight clients. The worry dialogues were qualitatively analysed, focusing on therapist and client processes in the task and also using observer‐based measures such as Classification of Affective‐Meaning States, Client Emotion Arousal Scale and Client Emotion Productivity Scale. Results: A tentative model of worry transformation using the two‐chair dialogue for worry is presented. The model consists of marker identification, enactment of the worry, deepening the toll of the worry, articulation of the need towards the worry and the worry softening or the client's standing up to the worry. The results also focus on the progression in the dialogues across the series of dialogues. Implications: The model has an immediate practical application as it can inform therapists' actions when working with worry processes in GAD clients. Implications for future research are also discussed. Abstract : A video abstract of this article can be viewed at:https://vimeo.com/182527407